2003
DOI: 10.1046/j.1440-1843.2003.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

SARS: epidemiology

Abstract: Severe acute respiratory syndrome (SARS) originated in Southern China in November 2002, and was brought to Hong Kong in February 2003. From Hong Kong, the disease spread rapidly worldwide but mostly to Asian countries. At the end of the epidemic in June, the global cumulative total was 8422 cases with 916 deaths (case fatality rate of 11%). People of all ages were affected, but predominantly females. Health care workers were at high risk and accounted for one‐fifth of all cases. Risk factors for death included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
510
1
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 633 publications
(527 citation statements)
references
References 15 publications
10
510
1
6
Order By: Relevance
“…Mice died of ARDS characterized by DAD and hyaline membrane formation within 3 to 4 days after intranasal infection (8,12). Both the development of ARDS and the increased pathogenic phenotype in older individuals are in complete agreement with data from human SARS-CoV cases (5,33). Two phases have been identified during SARS-CoV infection in humans (41).…”
Section: Vol 81 2007 Lethal Sars-cov Infection In Aged Mice 7417supporting
confidence: 60%
See 1 more Smart Citation
“…Mice died of ARDS characterized by DAD and hyaline membrane formation within 3 to 4 days after intranasal infection (8,12). Both the development of ARDS and the increased pathogenic phenotype in older individuals are in complete agreement with data from human SARS-CoV cases (5,33). Two phases have been identified during SARS-CoV infection in humans (41).…”
Section: Vol 81 2007 Lethal Sars-cov Infection In Aged Mice 7417supporting
confidence: 60%
“…Old age (over 60 years) was found to be significantly associated with SARS-related deaths (5,33). Death from SARS-CoV infection is most often due to rapidly progressive respiratory compromise (acute respiratory distress syndrome [ARDS]) and subsequent failure of multiple organs (50), and age is the only factor associated with the development of ARDS (4).…”
mentioning
confidence: 99%
“…This study describes the largest sample of confirmed MERS-CoV cases and confirms previous study findings indicating males are predominately affected by this disease [6,7] and is in comparison to Severe Acute Respiratory Syndrome (SARS), where there is a predominance of females in all cases [8]. Healthcare workers were at high risk and accounted for one-sixth of all cases, in comparison to SARS in which healthcare workers accounted for one-fifth of all cases.…”
Section: Discussionsupporting
confidence: 86%
“…During this epidemic 916 patients died of the disease and 8,422 were infected [153]. A new coronavirus (SARS-CoV) was found to be the etiological agent within 4 months of disease emergence [123,154,155] and its genome was completely sequenced within two weeks.…”
Section: Sarsmentioning
confidence: 99%